The Influence of Net Profit and Operating Cash Flow on Share Prices in Telecommunication Companies Listed on the Indonesian Stock Exchange - Anwar, Akifah Fikriah; Idris, Hariany; Sahade (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to: determine the partial influence of net profit and operating cash flow on stock prices, and determine the simultaneous influence of net profit and operating cash flow on stock prices. The variables in this study are stock prices as the dependent variable (Y), measured by the closing stock price at the end of the trading day, net profit as an independent variable (X1), measured by pre-tax net profit minus income tax, and operating cash flow as an independent variable (X2), measured by the difference between cash inflows and cash outflows. The population of this study consists of telecommunication companies listed on the Indonesia Stock Exchange, while the sample consists of 10 telecommunication companies selected using purposive sampling technique. Data collection is conducted through documentation techniques. This study uses multiple linear regression analysis to examine the relationship between net profit, operating cash flow, and stock prices. The data used are the financial data of telecommunication companies listed on the Indonesia Stock Exchange during the period 2020-2022. This research employed multiple linear regression analysis to examine the relationship between net profit, operating cash flow, and stock prices. The data used were the financial data of telecommunication companies listed on the Indonesia Stock Exchange during the period 2020-2022. Data analysis was carried out using multiple linear regression analysis. The results of this study showed Y = 2331.185 + 3.218 X1 + 7.780 X2. Based on the analysis results, it can be concluded that net profit has a significant partial effect on stock prices. Operating cash flow also has a significant partial effect on stock prices. Furthermore, it can be determined that both net profit and operating cash flow simultaneously have a significant effect on stock prices.